Movements of Long-Term Capital and the Adjustment Process - Roosa, Robert (The Review of Economics and Statistics, 1964)
T HROUGH the wide range of Professor Harris' contributions to economics -in his writing, his teaching, his creative role as an editor, and his participation in governmentone characteristic stands dominant among the many. He has injected the vitality of fresh inquiry into every pursuit to which his lively interests have led him. His two most recent careers, at the Treasury and in California, continue to offer the scope and the challenge which he has met with such incredible versatility through the Harvard years. And it is in the spirit of one who has learned much from him not only in trying to find answers but also in formulating questions -that I would like to add a few more questions to the many that he has posed, and the many he has answered, on the processes of payments adjustment. How many of us have, I wonder, been taunted by some of these same questions as we puzzled along our separate ways toward a reconciliation between text and teacher in those ever-changing, ever-lasting Haberler-Harris courses on international trade? And how few of us, at least among my own pre-war vintage, could have thought that the major uses we would find for all of this would be in attempting to find acceptable norms for avoiding the anarchy of unimpeded freedom, rather than for resisting the strangulation of autarky. The leading countries of the non-communist world are now all learning again to live with convertible currencies for current account, and some for capital account, transactions. Most have for more than a decade been committed to an orderly codification of procedures for limiting the constraints that individual countries place upon the flows of goods from one to another. But the vast area that is still left without systematic and comprehensive attention from governments, and for which there is as yet no satisfactory theoretical formulation to use as a starting point under today's conditions, is that of long-term capital movements. Much has evolved, to be sure, concerning short-term capital movements. An alert sensitivity is developing -aided by the increasingly close and frequent consultations among governments and central banks that the jet age now permits -to the sometimes delicate inter-relations between flows of short-term funds and the effectiveness of monetary policy in any country. As a result, a very thorough reappraisal has been set off, in nearly every one of the leading countries, examining the potentialities for a changing mix among monetary, fiscal, and incomes policies potentialities that take account of the requirements of external as well as internal balance. Both in government policy and in underlying economic theory, however, long-term capital flows continue to be the object mainly of improvised rationalization for whatever has been going on. Apart from various efforts to multilateralize development aid, there has not as yet been a sustained effort to work toward a consensus on the role of movements of longterm capital in the adjustment process. There has been interest, primarily among some of the international organizations, in working toward a codification of procedures. But that does not go to the fundamental need for a reconsideration of the influence that movements of long-term capital may be able to exert as a balancing force. That need has now become compelling in a convertible world of gradually freer trade, where general commitments to high employment, continuing growth, price stability, and fixed exchange rates effectively rule out other patterns of adjustment that were familiar in the textbooks, if not always in the practices, of earlier years. Regardless of their merit, these postwar commitments are, in fact, constraints on the ready correction of surpluses or deficits in the overall external accounts of the various leading countries. Indeed, it is very largely on this account that a plausible case has been made for the likelihood that periods of imbalance may